Effect of frequency on fade slope based on rain attenuation data measured in Malaysia - Islam, Md. Rafiqul; Chebil, Jalel; Khalifa, Othman Omran; Khan, Sheroz; Dao, Hassan; Zyoud, Al-Hareth (2010)
Wave propagation at higher frequencies is highly influenced by rain. The measured rain attenuation data was collected from January 1999 to April 2000 at 15, 23 26, and 38 GHz frequencies for terrestrial microwave links in Malaysia. This research investigated the effects of frequency on the fade slope. The fade slope was analyzed using the measured data and it is found that the distribution for the fade slope is similar for all four frequencies and independent of frequencies.